2017
DOI: 10.1161/jaha.116.005401
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Assessment of Sex‐Related Differences in Symptom Status and Health Perception Among Patients With Atrial Fibrillation

Abstract: BackgroundWe prospectively assessed sex‐specific differences in health perception, overall symptom status, and specific symptoms in a large cohort of patients with atrial fibrillation.Methods and ResultsWe performed a prospective multicenter observational cohort study of 1553 patients with atrial fibrillation. Patients completed questionnaires about personal characteristics, comorbidities, and symptoms on a yearly basis. Mean age was 70±11 years among women and 67±12 years among men. Health perception on a vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 30 publications
(34 reference statements)
2
46
0
3
Order By: Relevance
“…Most patients in the pathological ECG group suffered from AF or utter and the two most frequent mentioned symptoms were palpitations and dyspnoea comparable with studies dealing with symptoms in several thousand AF patients (13)(14)(15)(16). In our cardiac arrhythmia cohort chest pain took the third place of symptoms.…”
Section: Discussionsupporting
confidence: 82%
“…Most patients in the pathological ECG group suffered from AF or utter and the two most frequent mentioned symptoms were palpitations and dyspnoea comparable with studies dealing with symptoms in several thousand AF patients (13)(14)(15)(16). In our cardiac arrhythmia cohort chest pain took the third place of symptoms.…”
Section: Discussionsupporting
confidence: 82%
“…Our study further demonstrates that the symptom differences extend to worsened functional capacity among women with AF undergoing ablation. The gender differences in AF catheter ablation rates and reported symptom severity have been well described; however, less has been reported about the severity of symptoms among males and females with AF at the time of catheter ablation and how these symptoms may affect their decision to pursue an invasive rhythm control strategy. In this study, we found that women with AF undergoing catheter ablation reported a much higher symptom burden and more severe functional limitation than men.…”
Section: Discussionmentioning
confidence: 99%
“…6,13,15,16,[20][21][22] Existing literature likewise supports distinctive manifestations of AF symptoms between the sexes. Women with AF have been described to have more frequent and severe symptoms, [23][24][25][26][27] more atypical symptoms, 20,28 and to have a lower quality of life than men with AF. 25,27,29 As such, women have been described to be more likely to seek care for AF.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, prior studies have been limited by a narrow description of QOL based on visual analog scales and lack information on patients' concerns or satisfaction after their initial management. 6 Given the rapid increase in the burden of AF in Asian populations, 7 a deeper understanding of their symptom burden, QOL, and satisfaction with treatment is needed. This is of particular importance in Japan, where an aging society, which is more prone to AF, is becoming a public health concern.…”
Section: Introductionmentioning
confidence: 99%